The impact of play on child development - a literature review. Issue 5 (3rd September 2018) - Lai, Ngan Kuen; Ang, Tan Fong; Por, Lip Yee; Liew, Chee Sun
ABSTRACT: Play is never absent in human life, especially for children. The act of playing requires a game. Games can be divided into digital games and non-digital games. Digital games are games that utilise computers, mobile or handheld devices, or gaming console as playing platform while non-digital games may require physical contact and/or equipment which are not digital devices. This review aims at investigating the impact of non-digital games in child development studies for children within the ages of 4 to 9 years old. 43 papers were identified based on the proposed classification approach and analysed from the perspective of year, age group, type of play, research method, and learning outcome. The findings imply that non-digital games can stimulate the cognitive development of preschool age children.